Descriptive Qualitative Study on the Perception of Government Servants towards the COVID-19 Pandemic and SOPs Implemented in Public Places in Malaysia - Bilal Khairidzan; Ilya Natrah Mohd Nor; Najihah ‘Abidah Ab Razak; Tharshana Muraley; Abd Rahim Mohamed (Asian Journal of Medicine & Health Sciences, 2022)
Coronavirus disease (COVID-19) is a pandemic that has hit the world since 31st December 2019. It caused widespread increase in morbidity and mortality worldwide. Malaysia was one of the countries affected by this disease and the government has had to impose a Movement Control Order for citizens of Malaysia ever since March 2020. Restrictions and Standard Operating Procedures (SOPs) were introduced to curb and control the spread of COVID-19. These rapid lifestyle changes affected the lives of many Malaysians. This is a descriptive qualitative study aimed to study the perception, practices, and financial effects of COVID-19 on Malaysian government servants. The data was collected from 12 participants from the states of Selangor, Melaka, and Pahang. They were government officers in various government departments. The data was collected through in-depth semi-structured questionnaire interviews that was conducted through video calls. The interviews were conducted from October to December 2021. Three general themes emerged from the analysis: the respondents’ perception, the respondents’ actual practices, and financial implications. There were 13 sub-themes and 51 codes. The result of this study showed, all the respondents had good knowledge about COVID-19 and its SOPs while practising them, believing most of the Malaysian population is compliant with the government’s action, with a minority that opposes it, and that the participants were not affected financially by the pandemic.